Broadband near-infrared persistent luminescence of Ba[Mg2Al2N4] with Eu2+ and Tm3+ after red light charging. Issue 6 (23rd January 2019) - Ueda, Jumpei; Leaño, Julius L.; Richard, Cyrille; Asami, Kazuki; Tanabe, Setsuhisa; Liu, Ru-Shi
Abstract : A near infrared (NIR) persistent luminescent Ba[Mg2 Al2 N4 ]:Eu 2+ –Tm 3+ phosphor chargeable by red light was prepared via a solid state reaction from all-nitride starting materials. Abstract : A near infrared (NIR) persistent luminescent Ba[Mg2 Al2 N4 ]:Eu 2+ –Tm 3+ phosphor chargeable by red light was prepared via a solid state reaction from all-nitride starting materials. Rietveld refinement shows that the obtained sample correlated well with the standard. The Eu 2+ : 5d–4f broad persistent luminescence band in the range of 600–800 nm can be effectively obtained after charging in a broad wavelength selection range from UV to red light. The Tm 3+ acts as the NIR emission center, which consequently expands the persistent luminescence band from 600 to 830 nm due to the energy transfer from Eu 2+ to Tm 3+ . The sample could be charged using a red light emitting diode (LED), which indicates that the electron transfer process occurs from the lowest 5d level of Eu 2+ to electron traps through the conduction band. Owing to its features of red light charging and NIR persistent luminescence, the sample under ham with 1 cm thickness was charged by the red component of white light and its NIR persistent luminescence was detected even through the ham, which proves its potential use for biological imaging in the first biological window.